Development of an analytical method for the simultaneous determination of 22 Polycyclic Aromatic Hydrocarbons (PAHs) in maternal and umbilical cord blood - Swiha, Stéphanie; Pichon, Valérie; Fournier, Thierry; Gil, Sophie; Delaunay, Nathalie (Comptes Rendus. Chimie)
Pregnant women and their fetuses, a very fragile population, are exposed to polycyclic aromatic hydrocarbons (PAHs) and subject to potentially serious health risks. Consequently, the determination of PAHs in maternal serum and umbilical cord blood is necessary but challenging, due to their highly varied physico-chemical properties and trace presence. The aim of this project was to develop a method enabling, for the first time, the simultaneous determination of 22 listed PAHs from small volumes (100 ${μ }$L) of maternal serum and umbilical cord blood, including a sample pre-treatment reducing as far as possible the quantity of solvents used. A solid-phase extraction step on C18-grafted silica was optimized by studying the effect of different parameters (nature and proportion of organic solvent added to the sample, washing and elution conditions) on extraction yields. The evaporation step was carefully controlled to limit the loss of the most volatile PAHs. Then, to break any interactions between PAHs and serum proteins, a precipitation step prior to solid-phase extraction was optimized using a design of experiments. The final sample processing procedure led to extraction yields of between 27 and 57% and between 34 and 69% for 22 PAHs in serum and umbilical cord blood, respectively, with standard deviation values of less than 11%. Limits of quantification between 0.2 and 3.1 ${μ }$g/L were achieved for PAHs fluorescing in spiked real samples, close to the concentrations expected in biological samples.